Model Mediasi Kepuasan Konsumen Terhadap Loyalitas Pelanggan - Apriyanti, Rini; Dinovidta, Tio Lenta; Gunawan, Didik; Batubara, Rizki Wulanita (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the influence of price and reliability on consumer satisfaction and its implications for customer loyalty at PT. Tiki Jalur Nugraha Ekakurir (JNE) Batu Bara Branch. The research is motivated by the declining market share of JNE compared to its main competitor, J&T Express, which indicates potential issues in maintaining customer loyalty. This study employs a quantitative approach using non-probability sampling with a purposive sampling technique. Data were collected from 94 respondents who were active JNE customers and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with the assistance of SmartPLS 3.0 software. The results show that the variables of price and reliability do not have a direct significant effect on customer loyalty. This is indicated by the t-statistic value for price at 1.663 with a significance level (p-value) of 0.097, and for reliability at 0.529 with a p-value of 0.597—both below the threshold for significance (t > 1.96 and p < 0.05). Conversely, price and reliability significantly influence consumer satisfaction, with t-statistics of 3.939 (p = 0.000) and 3.167 (p = 0.002), respectively. Consumer satisfaction also has a direct significant effect on customer loyalty with a t-value of 5.701 and p = 0.000. Furthermore, consumer satisfaction acts as a mediating variable, as shown by the indirect effect of price on loyalty (0.267; t = 3.240) and reliability on loyalty (0.211; t = 2.759), both statistically significant. These findings affirm that consumer satisfaction is a key factor in building customer loyalty